Uncharged Components of Single-Stranded DNA Modulate Liquid–Liquid Phase Separation With Cationic Linker Histone H1 - Mimura, Masahiro; Tomita, Shunsuke; Sugai, Hiroka; Shinkai, Yoichi; Ishihara, Sayaka; Kurita, Ryoji (Frontiers in Cell and Developmental Biology, 2021)
Liquid–liquid phase separation (LLPS) of proteins and DNAs has been recognized as a fundamental mechanism for the formation of intracellular biomolecular condensates. Here, we show the role of the constituent DNA components, i.e., the phosphate groups, deoxyribose sugars, and nucleobases, in LLPS with a polycationic peptide, linker histone H1, a known key regulator of chromatin condensation. A comparison of the phase behavior of mixtures of H1 and single-stranded DNA-based oligomers in which one or more of the constituent moieties of DNA were removed demonstrated that not only the electrostatic interactions between the anionic phosphate groups of the oligomers and the cationic residues of H1, but also the interactions involving nucleobases and deoxyriboses (i) promoted the generation of spherical liquid droplets via LLPS as well as (ii) increased the density of DNA and decreased its fluidity within the droplets under low-salt conditions. Furthermore, we found the formation of non-spherical assemblies with both mobile and immobile fractions at relatively higher concentrations of H1 for all the oligomers. The roles of the DNA components that promote phase separation and modulate droplet characteristics revealed in this study will facilitate our understanding of the formation processes of the various biomolecular condensates containing nucleic acids, such as chromatin organization.